Effect of Ti addition and cast part size on solidification structure and mechanical properties of medium carbon, low alloy cast steel (Fracture and Structural Integrity, 2022)
In this work, the effect of Ti addition and the cast part size on the solidification structure and mechanical properties of a medium carbon, low alloy cast steel was analyzed. The experimental analysis involved the design of the melts by using Thermo-Calc® software, where different amounts of Ti added to a standard chemical composition of an AISI 13XX steel were simulated. Then, the solidification macrostructure (dendritic pattern and grain size) and microstructure were characterized by using conventional and specific metallographic techniques. Finally, the mechanical behavior in terms of hardness and tensile properties were evaluated.The results show that the addition of 0.12% of Ti promotes a fine dispersion of Ti nitrides and carbides, but when the Ti concentration raises to 0.2%, the size of the Ti nitrides and carbides increases while its amount decreases. Ti nitrides and carbides particles act as nucleation sites for the precipitation of ferrite from austenite, and it was found that the addition of Ti in the higher concentrations refines the solidification macrostructure (dendritic pattern) for both cast part sizes evaluated.Regarding mechanical properties, the addition of Ti does not significantly vary the ultimate tensile strength but reduces the total elongation for cast part sizes
Keywords: Cast steel; Solidification structure; Mechanical properties